Substitution and Haplotype Diversity Analysis on The Partial Sequence of The Mitochondrial DNA Cyt b of Indonesian Swamp Buffalo (Bubalus bubalis) - Akhmad Sukri; Mohamad Amin; Aris Winaya; Abdul Gofur (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2014)
This research aims to investigate the substitution pattern of nucleotide base and haplotype diversity of Indonesian swamp buffalo (Bubalus bubalis) based on the mitochondrial DNA cyt b partial gene sequence. 17 samples were chosen from 7 different regions with each uniquely represents Indonesian biogeography which comprise Aceh, Riau, Madiun, Blitar, Lombok, South Borneo and Tana Toraja. The result of cyt b gene sequence alignment showed the presence of transition and transversion substitutions and the absence of insertion and deletion. The amount of transitions was found to be higher than that of transversions and the amount of substitution in pyrimidine was also higher than that in purine. The highest amount of transitions happened in base TàC which is a silent substitution. The result of median joining network analysis showed that Indonesian haplotype Bubalus bubalis could be classified into 16 haplotypes which form different haplogroups unique to their geographical region. The result of median joining network analysis also indicated that the genetic relationships of swamp buffaloes (Bubalus bubalis) in Indonesia are highly influenced by their geographical locations.